Økonomiske konsekvenser af kommunalreformen - Houlberg, Kurt (Politik, 2016)
As part of the Danish Structural Reform of 2007, 239 municipalities were amalgamated to 66 municipalities, while 32 municipalities were left untouched. Evaluations based on difference-in-difference designs show that economic steerability has increased in amalgamated municipalities and that economies of scale regarding administration and maintenance of roads have been realised. The savings on administration and roads, however, have been reallocated to other policy areas, and no economies of scale for total expenditures can be identified. For major municipal policy areas such as day care, schools and eldercare – where the producing unit is at plant level rather than at municipal level – no economies of scale are seen. The efficiency of the service provision seems to be unaffected by the amalgamations. No valid conclusions can be drawn regarding cost-effectiveness effects of amalgamations and economies of scope related to an increased task portfolio.